Modeling on gas hydrate formation conditions in the Qinghai-Tibet plateau permafrost - Lu, Zhen Quan; Sultan, Nabil; Jin, Chun Shuang; Rao, Zhu; Luo, Xu Rong; Wu, Bi Hao; Zhu, You Hai (AGU, 2009)
Based on field investigated gas geochemistry and predecessors' data such as the permafrost ground temperature, thermal gradients within/below the frozen layer, the modeling on gas hydrate formation conditions is conducted in the Qinghai Tibet plateau permafrost. The modeled results show that the permafrost characteristics generally meet gas hydrate formation conditions in the study area. Gas composition, temperature-related permafrost parameters (e. g. permafrost thickness or its ground temperature and thermal gradients within / below the frozen layer) are the most important factors affecting gas hydrate occurrences, whose variance may cause the heterogeneity of gas hydrate occurrences in the study area. The most probable gas hydrate is the kind of hybrid of methane and weight hydrocarbon gases (ethane and propane). In the predicted gas hydrate locations, the upper gas hydrate occurrence depth may be around several ten to more than one hundred meters and the lower depth may range from several hundred meters to about one thousand meters and the thickness may reach several hundred meters. Compared with Canadian Mallik permafrost, the Qinghai-Tibet plateau permafrost has similar thermal gradients within / below the frozen layer and gas composition, except for relatively thinner permafrost, still suggesting great gas hydrate potentials.